EXPLORING THE THAILAND STUDENTS IN LEARNING BIPA: PERCEPTIONS AND CHALLENGES - Ni Wayan Krismayani; Putu Nur Ayomi; I Komang Budiarta (IKIP Siliwangi, 2024)
This research analyses Thai students' perceptions and challenges in learning BIPA. Research respondents for this study were 14 international students from Thailand who enrolled in Bahasa Indonesia bagi Penutur Asing (BIPA) at Universitas Mahasaraswati Denpasar. Observations, open-ended questionnaires, semi-structured interviews and classroom recordings were used to obtain data and analyzed using the descriptive qualitative method. The findings indicated that BIPA students encountered several challenges in language skills, language components and cultural and linguistic backgrounds. Therefore, simple instructions and examples are needed to help them learn the Indonesian language. Moreover, having more practice with Indonesian students also helps them understand the Indonesian language.